Hereditary spherocytosis concomitant with JAK2V617F-positive primary myelofibrosis: a case report - Qiu, Chi-E; Lei, Lei; Jiang, Guosong; Huang, Xiuqun; Li, Yadan (Frontiers in Oncology, 2025)
Hereditary spherocytosis (HS) is a genetic hemolytic disorder primarily characterized by hemolytic anemia, jaundice, splenomegaly, and frequent complications, including cholelithiasis, accompanied by the presence of spherocytes in the peripheral blood. This disorder predominantly follows an autosomal dominant inheritance pattern; however, certain cases exhibit an autosomal recessive mode of inheritance. HS is the most prevalent disorder associated with defects in the red blood cell membrane. Primary myelofibrosis (PMF), a chronic myeloproliferative neoplasm (MPN) characterized by splenomegaly resulting from extramedullary hematopoiesis, is associated with the JAK2 V617F mutation. Currently, there are no documented instances of co-occurrence of HS and PMF in the literature. We report the case of a 37-year-old male who experienced recurrent abdominal distension and splenomegaly over the past decade, along with elevated platelet counts over the past nine years. The patient tested positive for the JAK2V617F mutation, and bone marrow smears revealed the presence of teardrop-shaped erythrocytes. Peripheral blood smears indicated the presence of approximately 20% of spherocytes. The morphology of the bone marrow biopsy specimen was consistent with an MPN, classified as MF-2 grade. The highly specific eosin-5’-maleimide binding assay demonstrated a reduced mean fluorescence intensity of 25.73%. The patient was managed with aspirin and ruxolitinib and continued to be monitored through follow-up evaluations.